Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil - Carvalho de Lima, Tarcilla; Oliveira, Cléo Dilnei de Castro; Absalão, Ricardo Silva (European Journal of Taxonomy, 2020)
This paper describes rare Cardiomya species from Brazil which have been hitherto misidentified as Cardiomya cleryana (d’Orbigny, 1842) in literature or museum collections. Cardiomya minerva sp. nov. is proposed as new species and is characterized by its quadrangular shell, short and truncated rostrum, and external ornamentation composed of six radial ribs on the posterior half of the shell flank. Cardiomya striolata (Locard, 1897) described from the Mediterranean Sea and northwestern Atlantic Ocean, is reported from Brazil for the first time; although previously regarded as a junior synonym of Cardiomya costellata (Deshayes, 1835), it is herein considered as a full species and redescribed. This species is characterized by its trapezoidal shell flank, elongated rostrum, tapering towards the tip, and external ornamentation composed of 18–53 radial ribs, the 3–4 posterior ones being the strongest and more widely spaced. Other three previously unknown species are illustrated but not formally named due to the lack of well-preserved articulated shells.